Making evidence based medicine work for individual patients. (16th May 2016) - McCartney, Margaret; Treadwell, Julian; Maskrey, Neal; Lehman, Richard
Abstract : Margaret McCartney and colleagues argue that new models of evidence synthesis and shared decision making are needed to accelerate a move from guideline driven care to individualised care